Evaluation of crystallographic and electrical-superconducting features of Bi-2223 advanced ceramics with vanadium addition - Akkurt, Bahadır; Erdem, Ümit; Zalaoğlu, Yusuf; Ülgen, Asaf Tolga; Turğay, Tahsin; Yıldırım, Gürcan (SPRINGER, 2021)
In the current study, the effect of vanadium particles on the electrical, superconducting, crystallographic, key structural and morphological features of Bi1.8Sr2.0Ca2.2Cu3.0VxOy superconducting materials is examined with the aid of powder X-ray diffraction (XRD), scanning electron microscope (SEM), electron-dispersive X-ray (EDX) and dc electrical resistivity over the temperature (ρ-T). The vanadium-added Bi1.8Sr2.0Ca2.2Cu3.0VxOy (Bi-2223) superconducting materials are prepared within the molar ratios between x = 0.00 and 0.30 using the conventional solid-state reaction technique. The temperature-dependent electrical resistivity measurements show that the existence of vanadium atom in the superconducting system damages seriously the Bi-2223 (high-Tc) phase content in the crystal structure as a result of the formations/disappearances of new impurity phases. On this basis, the amplitude Ψ0 of wave function founded on the super-electrons is considerably reduced with the vanadium addition. The critical onset and offset transition temperature values truncate from the values of 110.92 K and 97.45 K to 103.17 K and 18.38 K in case of the maximum vanadium addition level of x = 0.30. Similarly, the XRD results present that the average crystallite size and c-axis length parameters are noted to decrease considerably whereas a-axis length, strain and relativistic dislocation density ratios are calculated to enlarge harshly depending on the addition content level. It is also obtained that the vanadium inclusions lead to increase seriously the permanent crystal structure problems, disorders, misorientations, lattice strains, crack-producing omnipresent flaws and grain boundary coupling problems in the active Cu–O2 consecutively stacked layers in the superconducting core, being assured by SEM analyses. Besides, the SEM results show that the enhancement of vanadium addition level in the crystal structure damages remarkably the flaky layers of platelet-like shape for the grains. In fact, the excess vanadium addition seriously damages the general characteristic view (flaky layer structure) of Bi-2223 compound. Based on the EDX findings, the main reason for the degradation of fundamental characteristic properties of Bi-2223 system may stem from the possible replacement of aliovalent vanadium impurities for the copper-sites in the crystal structure. Namely, the vanadium addition in the crystal structure is ploughed to improve the fundamental crystallographic and electrical-superconducting features of bulk Bi-2223 superconducting materials.